2022
DOI: 10.3389/fpsyg.2022.1037311
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of online learning amid the COVID-19: College students’ perspective

Abstract: Universities in China’s transition to online education in response to the COVID-19 pandemic have spawned several research studies. However, studies exploring college students’ technological skills, relationships with their peers and instructors, and collaborative learning experiences during the pandemic are scarce. Three aspects were explored in this mixed study: (1) changes in students’ engagement in class and the main factors involved; (2) students’ feelings and reactions during online learning; and (3) how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 55 publications
2
4
0
2
Order By: Relevance
“…The European Medical Student Association (EMSA) surveyed 11 countries on experiences during the pandemic [ 21 ], highlighting a low level of student involvement in decision-making, absence of a feedback mechanism and lack of quality resources. Similar data is reported in many Asian countries [ 20 , 22 , 23 ] and, in two comprehensive global reviews [ 26 , 27 ].…”
Section: Introductionsupporting
confidence: 88%
“…The European Medical Student Association (EMSA) surveyed 11 countries on experiences during the pandemic [ 21 ], highlighting a low level of student involvement in decision-making, absence of a feedback mechanism and lack of quality resources. Similar data is reported in many Asian countries [ 20 , 22 , 23 ] and, in two comprehensive global reviews [ 26 , 27 ].…”
Section: Introductionsupporting
confidence: 88%
“…This finding aligns with Xia et al (2022), which advocated for universities to conduct seminars and lectures to caution the youth against the threats of incitement and extremism prevalent on YouTube channels and Twitter.…”
Section: Testing the First Hypothesissupporting
confidence: 81%
“…This indicates less concern for parents regarding the distance learning method, as indicated by their answer that distance learning affected their children's academic performance, which revealed that parents are aware of the challenges associated with distance education and its potential impact on learning outcomes. Several studies examined the experiences of students during the transition to distance learning amid the pandemic [32][33][34] and many of them found that a considerable number of participants preferred face-to-face learning due to factors such as declines in children's learning motivation and cognitive abilities. Students faced challenges in distance learning such as a lack of engagement, difficulty in understanding complex topics, and a decrease in academic performance compared to face-to-face learning.…”
Section: Discussionmentioning
confidence: 99%